(3GdCHYGO GdbGfhfjI ddQbGHI Ydi GdJOGhd ai HhQUI GdChQGb GdeGdjI GdeUQjI (B/ s - (3CMeO EHQGgje THd MLGRis; (3gGfi SQi GdOjf s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3jJVef fWGb GdHMK ai gPg GdOQGSI HjGf GdfXe GdbGfhfjI GdJi JMce eYGedGJ GdJOGhd ai HhQUI GdChQGb GdeGdjI GdeUQjI HcGaI CTcGdgG(B: (3hcjajI GdQbGHI YdjgG hYdi GdeeGQSGJ ZjQ GdeTQhYI HgG (B- (3Yf WQjb GdLgGJ GdeNJnqUI HPdc(B: (3hai ebOeJgG GdgjFI GdYGeI ddQbGHI GdeGdjI (B- (3hGdJi JYO HeKGHI ENdGdkG HGdCMcGe GdNGUI HbGfhf Shb QCS GdeGd(B: (3hPdc ai VhA GdGQJHGW Hjf cmqd ef Shb GdEUOGQ(B: (3hShb GdJOGhd(B. (3hCf GdQbGHI Ydi eYGedGJ GdJOGhd HHhQUI GdChQGb GdeGdjI JSJgOa VeGf GdJcGaD Hjf GdeJYGedjf Ydi GdChQGb GdeGdjI(B: (3hGdMO ef GdeNGWQ ZjQ GdJLGQjI(B: (3hQaY OQLI caGAI GdShb(B: (3hGdefGaSI GdYGOdI(B: (3hGdJCcO ef MeGjI Mbhb GdeJYGedjf Ydi Jdc GdChQGb(B: (3hYOe hLhO Ci JdGYH Ch GSJaGOI ef eYdheGJ OGNdjI CKfGA Jdc GdeYGedGJ(B: (3hCfgG JMhd Ohf bjGe GdeJYGedjf HGdHhQUI HCYeGd ZjQ eTQhYI(B: (3Ch ZjQ CNdGbjI s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb bSe GdbGfhf GdJLGQi, (B2017s
(3HHdjhLQGajG(B: (3UaMGJ (B298-310 s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdHhQUIs; (3JOGhd GdGhQGb GdeGdjIs; (3Shb GdGhQGb GdeGdjIs; (3eHOG MQjI GdJOGhds; (3GdGaUGM Yf GdeYdheGJs; (3GdgjFI GdYGeI ddQbGHI GdeGdjIs; (3TQcI GdSeSQIs; (3TQcI GdGjOGY hGdbjO GdeQcRis; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs